The Effect of Economic Growth, Inflation and Human Development Index on Unemployment Rate - Listiawati, Hariyani (Robust: Research of Business and Economics Studies, 2024)
Unemployment is the most crucial problem in an economy, the problem of unemployment occurs as a result of an imbalance between available jobs and the number of labor force which increases every year. This research was conducted to find out how much influence economic growth, inflation, and the human development index have on the unemployment rate in the city of Kendari in 2012-2021. This research is a quantitative study using secondary data in the form of time series data. Secondary data obtained from the Central Bureau of Statistics. The analytical method used is path analysis method. The magnitude of the influence caused by the three variables of economic growth (X1), inflation (X2), and the human development index (X3) on the unemployment rate (Y) is 50.9%, while the remaining 49.1% is influenced by other variables outside of this research.